Near Infrared Light Triggered Photo/Immuno-Therapy Toward Cancers - Xu, Xiaoxue; Lu, Hongxu; Lee, Ruda (Frontiers in Bioengineering and Biotechnology, 2020)
Nanomaterials-based phototherapies, mainly including photothermal therapy (PTT), photodynamic therapy (PDT) and photoimmunotherapy (PIT), present high efficacy, minimal invasion and negligible adverse effects in cancer treatment. The integrated phototherapeutic modalities can enhance the efficiency of cancer immunotherapy for clinical application transformation. The near-infrared (NIR) light source enables phototherapies with the high penetration depth in the biological tissues, less toxic to normal cells and tissues and a low dose of light irradiation. Mediated via the novel NIR-responsive nanomaterials, PTT and PDT are able to provoke cancer cells apoptosis from the generated heat and reactive oxygen species, respectively. The released cancer-specific antigens and membrane damage danger signals from the damaged cancer cells trigger immune responses, which would enhance the antitumor efficacy via a variety of immunotherapy. This review summarized the recent advances in NIR-triggered photo-/immune-therapeutic modalities and their synergistic mechanisms and applications toward cancers. Furthermore, the challenges, potential solutions and future directions of NIR-triggered photo-/immunotherapy were briefly discussed.